PENGARUH RATIFIKASI PROTOKOL KYOTO TERHADAP KERJASAMA EKONOMI JEPANG-INDONESIA - Zailany Fadly Azmy; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes about the effect of Kyoto Protocol Ratification toward economy partnership agreement Japan-Indonesia. Economy partnership agreements between Japan and Indonesia have a significant progress not only in trading but also investment.The research method applies qualitative descriptive method, liberalism perspective and Foreign Direct Investment theory. The author collected data from books, encyclopedia, journal, mass media and website to analyze the effect of Kyoto Protocol Ratification toward economy partnership agreement Japan-Indonesia.The conclusion of this research is Japan-Indonesia Partnership Agreements increasing number of environmentally friendly investment in Indonesia through JCM project. Through this JCM project, Japan and Indonesia could to enforce the purpose of Kyoto Protocol. So that, the economy agreement Japan-Indonesia aside from to grant advantages for both of this Country, but also grant the good effect for the environment.Key words: Kyoto Protocol, Investment, Trade, Economy partnership agreement , environmentally friendly, JCM Project.